Komunikasi Krisis PT. Indonesia Asahan Aluminium Berkaitan Perbedaan Interpretasi Perhitungan Pajak Air Permukaan - Irene Silviani; Jannatun Nisa (PERSPEKTIF, 2022)
This study analyzes the political marketing strategy carried out by the Surya-Taufik pair who are the incumbent pair in participating in the simultaneous regional head elections (Pemilukada) in 2020 in Asahan Regency. The involvement of the incumbent pair in regional head elections is often seen as a strong candidate, this happens because the incumbent pair is considered to have had more dominant political capital such as popularity, network and image. The incumbent pair is considered to have a good image as a popular official in the eyes of the public, especially if it is supported by the performance of a positive figure, it will certainly strengthen the relationship between voters and candidate pairs in terms of winning. The theories used to explain these problems are democracy theory, political marketing theory, political communication theory and role theory. From the search results of researchers in the field, researchers get a summary of the flow of the process of winning the Surya-Taufik candidate pair, namely the process of candidacy, forming a winning team, conducting research, designing political products, implementing political products, establishing political communication and building commitment. The political marketing theory carried out by the Surya-Taufik pair uses three approach models, namely push marketing, pull marketing and pass marketing in conducting political campaigns. This strategy is a comprehensive step taken by the Surya-Taufik couple and the success team that can be accepted by all circles of society.